МОДУСНИ ЖАЛОНИ НА МОДЕЛА, ОРИЕНТИРАН КЪМ ПОДОБРЯВАНЕ НАФИНАНСОВО-ИКОНОМИЧЕСКО СЪСТОЯНИЕ И УДОВЛЕТВОРЕНОСТТА НАПАЦИЕНТИТЕ НА „МБАЛ-ПАЗАРДЖИК” АД - Temnilov, Krasimir (E-Journal VFU, 2024)
To reach an optimal level for organizational independence of all clinical structures under conditions of effective self-control and control of financial and medical indicators, as well as to ensure the application of the newly established medical standards in specialties represented in the hospital by achieving optimal indicators for medical equipment, optimal organization and number of personnel modern conditions require adaptation and improvement of the financial management and control system of the medical facility through a clearly defined control environment, risk management procedures, adequate and effective control activities, a monitoring system and provision of the necessary information and its continuous exchange at all units and structural levels.
Keywords: MBAL "Pazardzhik"; medical centre; medical services; finance; patient satisfaction